Divine Concepts, Tawhid, and Algorithmic Thinking: A Comparative Analysis of Christian and Islamic Perspectives on Educational Theology in the Era of Artificial Intelligence - Arhanuddin Salim; Rukmina Gonibala; Ishak Talibo; Mastang Ambo Baba (Universitas Pesantren Kh abdul Chalim Mojokerto, 2026)
The rapid integration of Artificial Intelligence (AI) into educational environments has generated significant ethical and pedagogical challenges, particularly for faith-based schools that must balance technological innovation with deeply rooted theological commitments. While global research has examined AI’s pedagogical potential, limited attention has been given to how religious educational institutions interpret and regulate AI through their theological worldviews. This study aims to investigate how Christian educational theology, grounded in the Imago Dei, and Islamic educational theology, rooted in Tawhid and Akhlak, shape institutional policies, classroom practices, and ethical decision-making related to the use of AI. A qualitative comparative case study was conducted at SMA Katolik Frater Don Bosco and MAN Model Manado using classroom observations, semi-structured interviews, and document analysis. The findings reveal that both schools adopt similar governance principles, including restricting AI autonomy in evaluative decisions, safeguarding human dignity, emphasizing a character-centered pedagogy, and using AI primarily to support rather than replace relational teaching roles. Although grounded in distinct theological traditions, both institutions articulate ethical boundaries that foreground human responsibility, moral intention, and personal interaction as essential elements of learning. These results demonstrate that religious traditions offer robust moral infrastructures for developing human-centered “algorethics” and provide contextually grounded insights that can enrich national and global discussions on the ethical implementation of AI in education.